A Phenomenological Study of Nursing Students' Experience in Clinical Practice When The Post Covid-19 Era - Jeanny Rantung; Evelyn Hemme Tambunan (Jurnal Gema Keperawatan, 2023)
Clinical practice is a pivotal requirement in nursing education to shape professional nurses. The Covid-19 pandemic has interfered with the effectiveness of clinical practice processes. Yet it must be a starting point to create a better clinical learning environment. The aim of this study is to explore the experiences of nursing students in engaging clinical practice in the era of post Covid-19 pandemic. A descriptive phenomenological approach was used to collect data from individual in-depth interviews from 18 March to 10 April 2023 using purposive sampling technique. Ten nursing students were interviewed in depth and audio-recordings were transcribed verbatim. Colaizzi's seven-step descriptive phenomenological methodology served as the basis for data analysis. Lincoln and Guba criteria were applied to assure the trustworthiness of this study. Four main themes were generated: initial feeling of clinical practice in post Covid-19 era, challenges in theory-practice gap, clinical practice environment, grateful for the opportunity to conduct clinical practice offline. The findings of this study are useful for nursing education together with the clinical field to facilitate a supportive clinical learning environment to enhance clinical engagement of nursing students. There is a need for scrutinizing factors that hinder or enhance the clinical learning process of nursing students. Studies on what makes nursing education and clinical fields involve deeply in students' clinical practice and learning while others do not are also pertinent.